Spatial domain communication technique for future chipless ID sensors based on vortex terahertz beams generated by metasurfaces - Seyed Ehsan Hosseininejad; Mohsen Khalily; Fan Wang; Rahim Tafazolli (Results in Physics, 2022)
As future communication systems move toward the terahertz (THz) spectrum with a much higher speed and more densification, enhanced security utilizing the novel concepts will be inevitable, particularly in automated identification systems. This paper proposes a novel spatial domain technique based on vortex beams generated by metasurface structures for efficient chipless identification (ID) sensors where the information is saved in the vortex modes. This approach using the vortex concept offers the high security strength in the automated systems compared to existing solutions, including time-based and frequency-based sensors. Furthermore, combining these vortex-based sensors and conventional ones results in substantially increasing the stored information capacity. To verify the idea, here, we present an uneven dielectric metasurface (UDM) to generate distinct vortex modes to identify different information. The proposed sensor is designed by using an equivalent transmission line (TL) model, and the extracted results exhibited a good agreement between simulation and theoretical approaches. Furthermore, it is demonstrated that the transmitted information capacity can be notably enhanced by using a sensor tag with simultaneous multiple modes and also using more than one tag simultaneously.